1974
DOI: 10.1093/oxfordjournals.aje.a121603
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Study of the Relationship of Reproductive Experience to Cancer of the Ovary1

Abstract: epidemiologic study of the relationship of reproductive experience to cancer of the ovary. Am J Epidemiol 99: 190-209. 1974.-From June 1957 to September 1965, all patients entering the Roswell Park Memorial Institute in Buffalo, New York, completed a questionnaire providing detailed information on demographic and social attributes, family history, radiation exposure, menstrual and reproductive characteristics and personal habits. Over 400 cases of ovarian cancer were admitted. These, combined with control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
2

Year Published

1975
1975
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(52 citation statements)
references
References 8 publications
4
46
0
2
Order By: Relevance
“…A lower frequency of hysterectomy, of unilateral oophorectomy, or of both among cases compared to controls has also been reported from several other studies (Wynder et al, 1969;Joly et al, 1974;Annegers et al, 1979;McGowan et al, 1979;Franceschi et al, 1982;Cramer et al, 1983). As these studies were case-control in design, there may have been some misclassification of controls who, rather than having a hysterectomy with ovarian conservation, actually had a hysterectomy with bilateral oophorectomy.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A lower frequency of hysterectomy, of unilateral oophorectomy, or of both among cases compared to controls has also been reported from several other studies (Wynder et al, 1969;Joly et al, 1974;Annegers et al, 1979;McGowan et al, 1979;Franceschi et al, 1982;Cramer et al, 1983). As these studies were case-control in design, there may have been some misclassification of controls who, rather than having a hysterectomy with ovarian conservation, actually had a hysterectomy with bilateral oophorectomy.…”
Section: Discussionsupporting
confidence: 68%
“…The raised risk for women with a first pregnancy after 35 years persisted (RR = 3.9, 95% CI 1.1-14.2). Results from other studies regarding the risk for women having a first child at relatively older ages are inconclusive, some finding no association (Newhouse et al, 1977;Casagrande et al, 1979;Cramer et al, 1983;Lesher et al, 1985), others an increased risk (Joly et al, 1974;McGowan et al, 1979;Hildreth et al, 1981;Franceschi et al, 1982). Only Franceschi et al (1982) found the increased risk to be statistically significant and independent of parity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Epidemiological studies have indicated that ovarian cancer is more common in women with lower mean number of pregnancies, in those never pregnant and in those with a history of infertility. 39 Early age of marriage and multiple pregnancies is the norm among Saudi females and this seems to have a protective effect. Low prevalence of cervical cancer in Saudi Arabia has been attributed to lack of sexual promiscuity and male circumcision, although Rabadi has reported a rising incidence from the Dhahran Health Center.…”
Section: Discussionmentioning
confidence: 99%
“…In line with both the 'incessant ovulation' and the 'gonadotrophin' hypotheses, pregnancy is expected to reduce the risk of epithelial ovarian cancer. One of the most consistent findings in ovarian cancer epidemiology is the protective effect of full-term pregnancies on epithelial ovarian cancer risk (Joly et al, 1974;Newhouse et al, 1977;Annegers et al, 1979;Casagrande et al, 1979;Miller et al, 1980;Hildreth et al, 1981;Byers et al, 1983;Cramer et al, 1983;Nasca et al, 1984;Tzonou et al, 1984;Voigt et al, 1986;Wu et al, 1988;Kvåle et al, 1988;McGowan et al, 1988;Mori et al, 1988;Booth et al, 1989;Franceschi 1989;Hartge et al, 1989;Shu et al, 1989;Gwinn et al, 1990;Negri et al, 1991;Lund, 1992;Whittemore et al, 1992;Chen et al, 1992;John et al, 1993;Polychronopoulou et al, 1993;Adami et al, 1994;Baker & Piver, 1994;Risch et al, 1994;Albrektsen et al, 1996). Parous women compared to nulliparous have relative risk estimates in the range of 0·3-0·7 (Annegers et al, 1979;Casagrande et al, 1979;Mori et al, 1988;Shu et al, 1989;Negri et al, 1991;Whittemore et al, 1992;Polychronopoulou et al, 1993).…”
Section: Parity and Pregnancymentioning
confidence: 97%